PENGARUH PROFITABILITAS, BEBAN PAJAK KINI, DAN ASET PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2017-2020 - Rifaldo Purba; Lorina Siregar Sudjiman (Jurnal Ekonomis, 2021)
The purpose of this study is to analyse the effect of profitability, current tax expense, and deferred tax assets on earnings management. The research data were obtained from manufacturing companies in the non-cyclical industrial sector of the food and beverage sub-sector listed on the Indonesia Stock Exchange. There are 10 companies out of a total of 63 companies studied using a 4-year period (2017-2020). The method used in this study is a descriptive method using a quantitative approach. The results of this study indicate that simultaneously profitability, current tax expense, and deferred tax assets have a significant effect on earnings management. While partially found that profitability and current tax expense have no effect on earnings management. In contrast to deferred tax assets which partially have a significant effect on earnings management.